Saturation of NO3- uptake in prairie streams as a function of acute and chronic N exposure. - O'Brien, Jonathan M.; Dodds, Walter K. (My University, 2011)
We conducted a series of stepwise NO3- additions to investigate the response of NO3- uptake to short-term (acute) changes in N concentration in 3 prairie streams. Observed NO3- uptake rates increased with short-term elevations in NO3- concentration and were consistent with linear and Michaelis–Menten kinetics models. We compiled these data with uptake rates from additional published studies to calculate robust estimates of N uptake kinetics for prairie streams. Half-saturation coefficients based on compiled data were 6.7 mg/L for NH4+ and 67 mg/L for NO3- = N. This difference in halfsaturation coefficients suggests that NH4+ is more efficiently assimilated than NO3-, indicating a preference for NH4+ as an N source. Similarly, ambient concentrations of NH4+ and NO3- were less than their respective half-saturation coefficients, and aerial uptake rates were generally ,5% of the maximum, suggesting severe limitation of N uptake at ambient conditions. The observed pattern of uptake kinetics suggests that physiological constraints limit biotic N uptake in these low-N streams and contrasts with the pattern of uptake observed in streams with chronically elevated ambient NO3- concentrations.
Keywords: Nitrate uptake; Biogeochemistry; Konza Prairie; Kings Creek